Natural Approach OR Cognitive Method? The Teaching of Spanish as a Second Language - Serrano Romero, Enriqueta Claudia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
In the United States, typically since the 1970s, among the instructors dedicated to the teaching of a Second Language (L2) there is a great dilemma that may be caused by an apparent pedagogical confusion about the term competence and the teaching of grammatical rules. Cognitive approach has been feasible and current alternative for teaching a second language. However, literature in the field shows that teaching a foreign language is much more complex aspect than a simple choice. Also, it has been perceived that the student's purpose is not only using the language in regular basis of communicating but also in academic and professional settings. Second language learners must distinguish between acquiring a language and learning it.